The odyssey of the Sangil in Mindanao - Non, Domingo M. (2011)
This paper attempts to trace the coming of the Sangil people in southern Philippines from Indonesia. The findings of the study show that they originally came from the islands of Ternate and Sangir/Sangehere to evade conversion to Christianity and had spread in different parts of Mindanao since their arrival.
Includes bibliographical references (pages 91-93).